Review of water-nanofluid based photovoltaic/thermal (PV/T) systems - Nur Farhana Mohd Razali; Ahmad Fudholi; Mohd Hafidz Ruslan; Kamaruzzaman Sopian (Institute of Advanced Engineering and Science, 2019)
Solar energy is secure, clean, and available on earth throughout the year. The PV/T system is a device designed to receive solar energy and convert it into electric/thermal energy. Nanofluid is a new generation of heat transfer fluid with promising higher thermal conductivity and improve heat transfer rate compared with conventional fluids. In this review, the recent studies of PV/T using nanofluid is discussed regarding basic concept and theory PV/T, thermal conductivity of nanofluid and experimentally and theoretically study the perfromance of PV/T using nanofluid. A review of the literature shows that many studies have evaluated the potential of nanofluid as heat transfer fluid and optical filter in the PV/T system. The preparations of nanofluid play an essential key for high stability and homogenous nanofluid for a long period. The thermal conductivity of nanofluid is depending on the size of nanoparticles, concentration and preparation of nanofluids.